The Influence of Animated Video Educational Media on Increasing Knowledge about Human Papillomavirus (HPV) Immunization among School-Aged Children - Fahriani, Nadiya; Jiwantoro, Yudha Anggit; Sumartini, Ni Putu; Emilyani, Desty (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Cervical cancer, the leading cause of death for women in developing countries, is now threatening adolescents aged 21-22 years due to HPV infection and lack of knowledge about prevention through vaccination. In Indonesia, cases and deaths from cervical cancer are relatively high, although the prevalence in NTB is lower. HPV immunization coverage in NTB is still 38,99% of the target of 90%, especially at the elementary school level such as MI Nurul Islam, where low student understanding and parental rejection are obstacles. This research seeks to determine the influence of Animated Video Education Media on HPV knowledge among children aged 10-11 years in MI Nurul Islam, which is in the working area of ​​Karang Pule Health Center. The research is a pre-experimental type with a pretest-posttest design; the total sampling approach determined that the research sample consisted of 40 individuals. By comparing students' knowledge before and after the intervention, the Wilcoxon test with α = 0,05 is used to examine how well video increases knowledge regarding HPV vaccination. The study's findings demonstrated that respondents' knowledge of HPV vaccination was 65% in the poor category prior to receiving the video, and 92.5% in the good category following the video. This was demonstrated by an average increase from 49.25 to 91 with a P-Value (0,000 <0,05). This means that there is an effective video about HPV towards the Level of Knowledge of Children Aged 10-11 Years in MI Nurul Islam, Karang Pule Health Center, Working Area. The results of the study are expected to provide benefits for respondents, future researchers, educational institutions, and research sites.